Analisis Lingkungan Kerja Dalam Meningkatkan Kinerja Pegawai Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Kota Bogor - Nesa Arnanda Nursahi; Noto Susanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of the noisy working environment and less effective communication on the performance of employees of the Bogor City Women's Empowerment and Child Protection Office. The research method used is qualitative. Data collection is done through observation, interviews, and documentation. Research results show that noise in the working environment interferes with employee concentration. In addition, less effective communication causes miscommunication and delays in decision-making. This study concluded that the improvement of the working environment, especially in noise reduction and increased communication effectiveness, is an important step to improve the performance of employees of the Bogor City Women's Empowerment and Child Protection Office.